2019
DOI: 10.1002/sd.1982
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and economic performance: Gaps and trends for future research

Abstract: The aim of this paper is to determine the existence of gaps in the literature, by investigating studies that statistically analyzed the relationship between sustainable development and economic performance. A literature review was conducted in the Web of Science and Scopus databases. The study analyzed the authors, publication years, journals involved, methodologies used, and results obtained. The identified gaps and opportunities were (a) opportunity to create or employ different measurements for financial, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 85 publications
(315 reference statements)
3
24
0
Order By: Relevance
“…This in turn improves their environmental, social and financial performance. This study is supporting the findings of [53,65].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This in turn improves their environmental, social and financial performance. This study is supporting the findings of [53,65].…”
Section: Discussionsupporting
confidence: 92%
“…However, based on the dynamic capabilities approach, it is expected that organizations with SEO are being innovative, proactive and taking risks to make their production processes more efficient, leading to zero wastage and full utilization of resources. This will result in better economic performance [64,65]. Based on this justification, we propose that:…”
Section: Seo and Economic Performancementioning
confidence: 99%
“…Corporations play an important role in achieving the objectives of sustainable development by adopting business policies and practices that maximize shareholders' wealth, economic and social well‐being of its employees, and of the society in general without adversely affecting the environment (Mensah, 2019). Such activities of firms that contribute to sustainable development constitute corporate sustainability, which is the process of balancing economic, ecological, and social concerns (do Prado et al, 2020; Elkington, 1999). It is determined through the CSP of firms, which signifies how a firm's business activities impact the environment, society, and the overall economy.…”
Section: Introductionmentioning
confidence: 99%
“…It is determined through the CSP of firms, which signifies how a firm's business activities impact the environment, society, and the overall economy. This impact can be either positive or negative (do Prado et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The role of CSR in terms of the financial aspect of corporate social performance requires further comprehension and exploration, particularly in a developing country such as Pakistan, across all sectors, and consequently, sustainable growth can be envisioned (Rana & Asad, 2018). Prado et al (2019) explored future endeavors by identifying the existing gaps in literature using statistical analyses and employing variables or methods in existing studies on the current state of corporate social performance and corporate financial performance. They concluded that there is no overwhelming evidence that could lead to a relationship of truth, so the direction could be identified using the latest methods.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%